Identifikasi Kandungan Senyawa Formalin Pada Ikan Kering di Pasar Tradisional Sempo Pasangkayu - Nini Sahrianti S.; Israyana Israyana; Marlin Eppang; Nasrullah Nasrullah (FORIKES, 2021)
Formaldehyde is a colorless solution and smells very offensive, used as a food supplement, very dangerous, causes irritation, interferes with digestive tract and cause cancer. The purpose of this study is to understand of womb formaldehyde compounds in dried fish in the traditional market Sempo village of Pasangkayu. This study was an experiment with physical and chemical screening using a taste of tests. Sample size were 12 dried fish. The result physical examination that was marked by spotless, no flies, smell not typical of dried fish and its keep resistant texture. During chemical testing for a formaldehyde KIT, four dried fish contain formaldehyde, be marked with discolouration to purple in the sample solution. It was found that there were formalin contents in some dried fish revolve in the traditional sempo market Keywords: formaldehyde; dried fish ABSTRAK Formaldehida adalah larutan yang tidak berwarna dan baunya sangat menyengat, sebagai bahan tambahan makanan, sangat berbahaya, menyebabkan iritasi, mengganggu saluran pencernaan dan menyebabkan kanker. Tujuan penelitian ini adalah untuk mengetahui kandungan senyawa formaldehida pada ikan kering di Pasar Tradisional Sempo Desa Pasangkayu. Penelitian ini merupakan eksperimen dengan skrining fisik dan kimia menggunakan tes rasa. Sampel diambil dengan menggunakan total sampel sebanyak 12 sampel. Hasil pemeriksaan fisik yang ditandai dengan bersih, tidak ada lalat, bau tidak khas ikan kering dan teksturnya tahan simpan. Selama pengujian kimia untuk KIT formaldehida, empat sampel positif mengandung formaldehida, ditandai dengan perubahan warna menjadi ungu dalam larutan sampel. Kesimpulan Ditemukan kandungan formalin pada beberapa ikan kering yang beredar di pasar sempo tradisional. Kata kunci: formalin; ikan kering